Diabetic Patients and Peritoneal Dialysis - yassine Allata; Basmat Amal Chouhani; Ghita EL Bardi; Tarik Sqalli Houssaini; Nadia Kabbali (Bulletin de la Dialyse à Domicile, 2023)
The prevalence of diabetes mellitus (DM) among patients requiring renal replacement therapy (RRT) has been on the rise worldwide, with DM now being the primary cause of end-stage renal disease (ESRD) in roughly one-third of RRT initiations. Although renal transplantation is the optimal treatment for ESRD, its limited availability has led to in-center hemodialysis (HD) being widely used as the default RRT modality in many countries. However, peritoneal dialysis (PD) may offer a superior option for diabetic patients due to its slower ultrafiltration rate, which can help mitigate the dialysis-induced hypotension and coronary ischemia that are associated with extracorporeal circulation during HD. Despite these advantages, unfounded concerns about technique failure and increased complication rates have discouraged some clinicians from recommending PD as a first-line RRT for diabetic patients.